Peran Informasi Akutansi dalam Pengambilan Keputusan Manajemen Pada CV. ADG Medan - Aswin Akbar (Departement of Mathematics Education, 2023)
This research explores the role of accounting information in management decision making at CV. ADG Medan. The company operates in a variety of business sectors and has been around for more than three decades. This research discusses basic concepts about accounting systems, financial reports, financial management, and purchasing decision theory as a basis for understanding the role of accounting information in organizations. In this research, we highlight that accounting information acts as a language that communicates a company's financial condition and business results. CV. ADG has an organizational structure that focuses on line and staff, with an accounting department that is important in processing financial data. The importance of management decisions in organizations is also emphasized, with decisions being made relating to policies, procedures and regulations affecting various aspects of the company. In addition, this research notes the importance of considering non-financial factors in management decision making, following constantly changing external developments. Companies are also reminded to develop competent human resources and adopt relevant technology to increase their efficiency and effectiveness. This research provides insight into how accounting information influences management decision making at CV. ADG Medan, and provide recommendations to strengthen the role of accounting information in supporting the success and sustainability of companies.